Tests and developments of the PANDA Endcap Disc DIRC. (26th April 2016) - Etzelmüller, E.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Götzen, K.; Kalicy, G.; Krebs, M.; Lehmann, D.; Nerling, F.; Patsyuk, M.; Peters, K.; Schepers, G.; et al.
Abstract: The PANDA experiment at the future Facility for Antiproton and Ion Research (FAIR) requires excellent particle identification. Two different DIRC detectors will utilize internally reflected Cherenkov light of charged particles to enable the separation of pions and kaons up to momenta of 4 GeV/c. The Endcap Disc DIRC will be placed in the forward endcap of PANDA's central spectrometer covering polar angles between 5° and 22° . Its final design is based on MCP-PMTs for the photon detection and an optical system made of fused silica. A new prototype has been investigated during a test beam at CERN in May 2015 and first results will be presented. In addition a new synthetic fused silica material by Nikon has been tested and was found to be radiation hard.